The effects of acute doxorubicin treatment on proteome lysine acetylation status and apical caspases in skeletal muscle of fasted animals. Issue 3 (26th March 2013) - Dirks-Naylor, Amie J.; Tran, Ngan T. K.; Yang, Sendra; Mabolo, Raean; Kouzi, Samir A.
Abstract : Background: Doxorubicin treatment is known to cause muscular weakness. However, the cellular mechanisms have not been elucidated. We aimed to determine the effects of acute doxorubicin treatment on proteome lysine acetylation status, an indication of the apoptotic and inflammatory environment, and the expression and activation of various apical caspases involved in the initiation of apoptosis. Methods: Six‐week‐old male F344 rats were injected intraperitoneally with 20 mg/kg of doxorubicin or saline. Once the treatment was administered, both groups of animals were fasted with no food or water until sacrifice 24 h posttreatment. Results: Doxorubicin treatment affected neither the proteome lysine acetylation status nor the expression of sirtuin 1, sirtuin 3, SOD1, or SOD2 in soleus of fasted animals. Doxorubicin treatment also did not affect the expression or activation of procaspase‐1, procaspase‐8, procaspase‐9, or procaspase−12. Conclusion: We suggest that doxorubicin does not exert a direct effect on these catabolic parameters in skeletal muscle in vivo.